The Importance of Developing Multiple Intelligences Among Pupils at Inclusive Primary Schools - Kiswarday, Vanja; Cerovšek, Andreja (Revija za elementarno izobraževanje, 2025)
In this article, we explore the awareness of educational professionals regarding the use of Gardner’s theory of multiple intelligences (MI) in inclusive schools. The research involved 49 educational professionals from selected primary schools. We found that they were generally familiar with Gardner’s MI theory, but most do not use it intentionally in their teaching. They most often develop interpersonal, verbal-linguistic, and mathematical-logical intelligence, while bodily-kinesthetic, spiritual, and musical-rhythmic intelligences remain less frequently stimulated. In an inclusive school, it is crucial for teachers to use Universal Design for Learning, which addresses different types of intelligence and enables more differentiated teaching.